2022
DOI: 10.1186/s12937-022-00760-6
|View full text |Cite
|
Sign up to set email alerts
|

Iodine nutrition status and thyroid autoimmunity during pregnancy: a cross-sectional study of 4635 pregnant women

Abstract: Background Pregnant women in Shanghai have long been at risk for mild iodine deficiency. Because thyroid autoimmunity in pregnant women can lead to premature birth and miscarriage as well as neurodevelopmental deficits in the fetus, the aim of this study was to explore the association of iodine nutrition status with thyroid antibodies during pregnancy. Methods A pregnancy-birth cohort was conducted including 4635 pregnant women in Shanghai, China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In this study, the median UI of pregnant women was 148.40 mg/ L < 150 mg/L, indicating mild iodine deficiency in pregnant women in Fujian Province, which was similar to our previous study and the results in coastal China (3,17,35,36). Similar to provinces like Fujian, pregnant women in some developed countries also face iodine deficiency, such as those in Austria, Norway, and Sweden (37,38).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the median UI of pregnant women was 148.40 mg/ L < 150 mg/L, indicating mild iodine deficiency in pregnant women in Fujian Province, which was similar to our previous study and the results in coastal China (3,17,35,36). Similar to provinces like Fujian, pregnant women in some developed countries also face iodine deficiency, such as those in Austria, Norway, and Sweden (37,38).…”
Section: Discussionsupporting
confidence: 89%
“…Nearly 2 billion people worldwide still suffer from inadequate iodine intake (2). China used to have a high prevalence of iodine deficiency disorders (IDDs) (3).…”
Section: Introductionmentioning
confidence: 99%
“…In male subjects, the positive rates of TgAb and TPOAb were not affected by serum iodine levels, while in female subjects, lower serum iodine levels increased the positive rates of TgAb and TPOAb. A study on pregnant women also found that low serum iodine would increase the positive rate of TgAb, TPOAb [30]. The speci c reason is still unclear, and further research is still needed to clarify the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Urine collection and the iodine urinary test method were carried out according to the methods detailed in our published articles [ 18 ]. Iodine status was categorized as follows: insufficiency (urinary iodine concentration (UIC) less than 150 μg/L) (low UIC); adequate (UIC more than 150 μg/L and less than 249 μg/L); above requirements (UIC more than 250 μg/L) (high UIC) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%